SYNTHETIC FLUID INCLUSIONS IN THE SYSTEMS NACL-H2O AND NACL-CO2-H2O: DISSOLUTION TEMPERATURES OF HALITE - Nagaseki H.; Hayashi K.-I. (My University, 2006)
This study examined the effect Of CO2 on NaCl solubility in hydrothermal fluid, with the synthetic fluid inclusion technique. Fluid inclusions of 30-40 wt% NaCl and 5 mol % CO2 were synthesized, and their halite dissolution temperatures, Tm,(halite), were measured. The solubilities of NaCl in CO2-bearing aqueous fluid were obtained at 160-320°C under vapor-saturated pressures. The Tm(halite) value in aqueous fluid with 5 mol % CO2 obtained in this study agrees with that of Schmidt et al. (1995), showing that 5 mol % CO2 reduces the solubility of NaCl by about 1 wt%. Calculation of magnetite solubility suggests that 5-10 mol % CO2 decreases magnetite solubility by 4.5-8.9 % relative to the magnetite solubility in CO2-free solution. Therefore, an increase of CO2 content in ore-forming solutions may cause deposition of iron minerals and produce ore deposits.
Keywords: EFFECT OF CO2; HALITE SOLUBILITY; NACL-CO2-H2O SYSTEM; SYNTHETIC FLUID INCLUSION